2015
DOI: 10.5963/ijep0501001
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Performance Evaluation of Different Low-Tech Composter Prototypes

Abstract: Abstract-Decentralized composting has become a powerful option for municipal organic waste management. This technology, not only is an effective tool to treat organic waste, producing compost as a valuable by-product, but also represents an innovative way to involve waste generators in treatment operations. Decentralized composting contributes to reducing waste transportation, treatment costs and landfilling volumes thus resulting in a positive impact on municipal waste management programs. In this work, three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In previous work, as well as in other authors experiences, elevated EC values were observed in compost made from dining wastes. This is associated to the presence of cellulosic material in the feedstock, such as napkins and tablecloths made with paper (Arrigoni et al, 2015;Faverial and Sierra, 2014;Kalamdhad and Kazmi, 2009a;Kalamdhad and Kazmi, 2009b). However, in this study, the differences in the EC values between the upper and the lower layers of the composter, also would show leachates accumulation in the lower part of the composter; leachates frequently include dissolved salts and, thus, increase compost electrical conductivity.…”
Section: Compost Stability Indicators and Quality Monitoring Variablesmentioning
confidence: 71%
See 2 more Smart Citations
“…In previous work, as well as in other authors experiences, elevated EC values were observed in compost made from dining wastes. This is associated to the presence of cellulosic material in the feedstock, such as napkins and tablecloths made with paper (Arrigoni et al, 2015;Faverial and Sierra, 2014;Kalamdhad and Kazmi, 2009a;Kalamdhad and Kazmi, 2009b). However, in this study, the differences in the EC values between the upper and the lower layers of the composter, also would show leachates accumulation in the lower part of the composter; leachates frequently include dissolved salts and, thus, increase compost electrical conductivity.…”
Section: Compost Stability Indicators and Quality Monitoring Variablesmentioning
confidence: 71%
“…Since commercial compost bins volume usually range from 40 to 500 L, in these systems the thermal inertia is usually lower because the composting mass could not be enough to retain the metabolic heat generated during the composting active phase. Therefore, small-scale composting systems could have a poor performance in achieving USEPA PFRPs or other temperature sanitization standards or recommendations (Abdullah et al, 2013;Arrigoni et al, 2015;Benjawan et al, 2015;Iyengar and Bhave, 2006;Sánchez et al, 2015). In tropical and favourable climatic conditions or in controlled laboratory settings, small-scale composting has shown good temperature evolution performances (Barrena et al, 2014;Faverial and Sierra, 2014;Lleó et al, 2013;Varma and Kalamdhad, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, a thermophilic process is believed to accelerate composting. However, based on a study by Arrigoni et al (2015), a thermophilic process is not a guarantee for higher Table 2). The lower mass reductions might be due to the presence of lignin, which is relatively more degradable in aerobic environments but refractory in anaerobic ones (Komilis and Ham 2003).…”
Section: Mass Reductionmentioning
confidence: 99%